Effect on weight gain of routinely giving albendazole to preschool children during child health days in Uganda: cluster randomised controlled trial - Alderman, Harold; Konde-Lule, Joseph; Sebuliba, Isaac; Bundy, Donald; Hall, Andrew (BMJ, 2006)
To estimate the effectiveness of delivering an anthelmintic through a community child health programme on the weight gain of preschool children in Uganda. Participants 48 parishes participating in a new programme for child health: 24 offered children an additional service of anthelmintic treatment. The outcome is based on measurements from 27 995 children. Treatment of children aged between 1 and 7 years with 400 mg albendazole added to standard services offered during child health days over a three year period. Main outcome measure Weight gain.The provision of periodic anthelmintic treatment as a part of child health services in Uganda resulted in an increase in weight gain of about 10% (166 g per child per year, 95% confidence interval 16 to 316) above expected weight gain when treatments were given twice a year, and an increase of 5% when the treatment was given annually. Deworming of preschool children in Uganda as part of regularly scheduled health services seems practical and associated with increased weight gain.
Keywords: Child health days; Weight gain; Albendazole